CREATIVE PERSONALITY OF THE TEACHER IN PROFESSIONAL ACTIVITIES - Turlubaeva, D.K. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article defines the concept of "creative individuality of a teacher", reveals its importance in pedagogical activity, the influence of innovation in professional activities. The creative individuality of the teacher is characterized by the fact that due to the individual characteristics of its development (professional thinking, creative attitude to the cause, aspirations for self-realization). The professional activity of such a teacher differs from the work of his colleagues in the search for new original approaches and means. Bright representatives of creative
Keywords: pedagogical activity; creative individuality of the teacher